2015
DOI: 10.1016/j.rehab.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

The anterior mini-open approach for femeroacetabular impingement: Gait and functional assessment at one year post-surgery

Abstract: There was significant reduction in pain intensity 12 months following mini-open approach for FAI compared to preoperatively. Improvement in gait analysis and functional capacity was also seen, although not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The mean postsurgery follow-up was 28.1±15.5 months in 89% of studies that reported this variable. Follow-up ranged from 12 months25 28 to 73.2 months 49…”
Section: Resultsmentioning
confidence: 99%
“…The mean postsurgery follow-up was 28.1±15.5 months in 89% of studies that reported this variable. Follow-up ranged from 12 months25 28 to 73.2 months 49…”
Section: Resultsmentioning
confidence: 99%
“…Besides, neuromuscular adaptations have been reported to influence symptoms and contribute to changes in biomechanical outcomes 19,[29][30][31][32] . Although several studies reported on hip biomechanics in patients from pre-arthritic hip disease 20,27,[33][34][35][36][37] , the effect on musculoskeletal loading in terms of the dynamic muscle forces and hip contact force (HCF) is still limited to gait 32,37,38 with little information during functional ROM. As osteochondroplasty of the cam morphology can decrease joint contact loading by 21-27% 39,40 , a further understanding of changes in muscle forces and their consequent effect on joint loading may provide benefits to design better pre-and/or postoperative FAI rehabilitation programs after corrective FAI surgery 41,42 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported good results in the management of patients with FAI using an anterior Hueter approach. 5 , 20 , 29 , 30 However, the anterior Hueter approach might make it difficult to access the subspine space. Cohen et al 7 managed FAI in athletes using a direct mini-open approach and demonstrated significant improvement in functional outcomes.…”
Section: Discussionmentioning
confidence: 99%